ANALISIS BALANCED SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA PERBANKAN TAHUN 2021-2024 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dyah Shinta Kusumaningtyas; Stephanie Swastika Dwi Utami; Ade Irawan (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2025)
The purpose of this study is to determine the results of banking performance in 2021-2024 listed on the Indonesia Stock Exchange (IDX) when measured using the Balanced Scorecard approach. This study used quantitative descriptive statistical data analysis sourced from annual reports and financial reports of banks listed on the Indonesia Stock Exchange (IDX) in the period 2021-2024. The results of the study show that the measurement of financial perspective performance measured by ROA, ROE, NIM and BOPO overall performance is quite good. Measurement of customer perspective performance measured by Third Party Funds (DPK) for each period shows poor performance. Measurement of internal business process perspective performance measured by the number of ATMs for each period shows poor performance.